2017
DOI: 10.1177/1010428317698361
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics prediction and experimental validation of microRNA-20a targeting Cyclin D1 in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is the major form of primary liver cancer, which is the second and sixth leading cause of cancer-related death in men and women, respectively. Extensive research indicates that Wnt/β-catenin signaling pathway, which plays a pivotal role in growth, development, and differentiation of hepatocellular carcinoma, is one of the major signaling pathways that is dysregulated in hepatocellular carcinoma. Cyclin D1 is a proto-oncogene and is one of the major regulators of Wnt signaling pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…Overexpression of miR‐17‐5p has been shown to inhibit proliferation and trigger apoptosis . MiR‐20 has previously been associated with cyclin D1 and has been shown to be associated with vascular endothelial growth factor, a cytokine, via activation of Akt signaling . MiR‐27a‐3p has been shown to promote cell proliferation and invasion possibly through its association with the cytokine TRAIL (TNF‐related apoptosis‐inducing ligand) or through its effects on insulin .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR‐17‐5p has been shown to inhibit proliferation and trigger apoptosis . MiR‐20 has previously been associated with cyclin D1 and has been shown to be associated with vascular endothelial growth factor, a cytokine, via activation of Akt signaling . MiR‐27a‐3p has been shown to promote cell proliferation and invasion possibly through its association with the cytokine TRAIL (TNF‐related apoptosis‐inducing ligand) or through its effects on insulin .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Wnt/β‐catenin pathway has been observed in at least 1/3 of HCC, and a significant number of these have mutations in the β‐catenin gene . According to investigation, the Wnt/β‐catenin signaling pathway is involved in the growth, development, differentiation of HCC . A previous study demonstrated that the Wnt/β‐catenin signaling pathway regulates the protein expression of the angiogenic factors, MMP‐2, MMP‐9, VEGF‐A, VEGF‐C, and bFGF in HCC cells .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] It has also been demonstrated that miR-623 targeted cyclin D1 in gastric cancer cells. 7-12 Jiang et al 13 had revealed that miR-623 was downregulated in gastric cancer, and they further found that upregulation of miR-623 inhibited the proliferation in SGC-7901 and BGC-823 cells and enhanced the chemosensitivity of cells to 5-Fluorouracil.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is a key regulator in cell cycle and has been reported to be upregulated in HCC and thought to be a potential target for HCC. [26][27][28] It has also been demonstrated that miR-623 targeted cyclin D1 in gastric cancer cells. 13 In this study, we found that miR-623 could inhibit the cyclin D1 expression in HCC cells.…”
Section: Discussionmentioning
confidence: 99%